THE TORCH WAR TRADITION AS A MEDIA OF INTRODUCING LOCAL WISDOM FOR BIPA STUDENTS - Aliva Rosdiana; Olyvia Revalita Candraloka; Haryanto Haryanto; Hayu Dian Yulistiati; Aprilia Riyana Putri (Universitas Islam Nahdlatul Ulama Jepara, 2023)
The Torch War, as part of the Jepara culture, is a traditional ceremony held in the village of Tegalsambi, Tahunan, Jepara. Through cultural-based BIPA learning media, foreign students who learn Indonesia is expected to be closer to know about multiculturalism in Indonesia. This study uses a qualitative descriptive method through an anthropolinguistic approach to examine the culture and history of the Torch War as its object through an interview process through engaging, skilled, recorded and note-taking techniques The result of the study found that through cultural portraits, BIPA students have insight into the culture and beliefs of the Javanese people, especially the people of Tegalsambi Village, Jepara through meaning of symbols used in Torch War ceremony. The offerings used in Torch War ceremony symbolized were buffalo head, Sega Golong, Tumpeng kuning, Kupat, or ketupat, Dekem or Ingkung Ayam, Bubur abang Putih, Arang-arang Kambang, Jajan Pasar, Pisang Raja (Plantains), and Kembang. The sparks from the torch and symbols used in offerings are believed to avert harm and bring health. The symbols used in offering, BIPA students engages deeper existing local heritages and appreciating it as Indonesia’s national wealth through values, such as tolerance, affection, mutual cooperation, andhap ashor, humanity, respect, etc. Keywords: Torch War; Literature; Culture; BIPA; Diversity; Anthropolinguistics